Case Rate And Early Detection Of Pulmonary Tuberculosis Disease In Student At Elementary School 04 Lebak Bulus - Nanny Harmani (Syntax Corporation, 2022)
The age of children is an age that is very vulnerable to transmission of pulmonary tuberculosis. The highest rate of transmission is found in the 0-6 year age group and the 7-14 year age group. Various efforts were made to minimize the occurence of tuberculosis in children, such as the program of community health center in preventing and controlling pulmonary tuberculosis. The purpose of this study was early detection of pulmonary tuberculosis in Elementary School 04 Lebak Bulus. This type of research is cross sectional. Questionnaire as a method of data collection. The total population is 270 people with a sample of 37 people with convenience sampling technique. Univariate analysis with diagram. The result showed that were students who showed symptomps that lead to pulmonary tuberculosis disease (2,7%) and had risk factors for pulmonary tuberculosis disease (2,7%) from a total sample of 37 people. It can be concluded that there are students who have symptoms and risk factors for pulmonary tuberculosis disease at Elementary School 04 Lebak Bulus. Researchers suggest that further examinations be carried out in the form of rapid molecular test with sputum samples.